Selection of attributes for a classifier of telecommunication failures in the copper mine - Karaban, Bartłomiej; Korczak, Jerzy (Business Informatics, 2014)
Ensuring safety and continuity of production is the major task of telecommunication systems in deep mining. These systems, despite their use of modern and innovative infrastructure of monitoring solutions, are not free from imperfections. One of the practical problems are false alarms signaling the occurrences of damaged infrastructures. In the paper, the data sources of the telecommunication system are identified and described, as well as the methods of their preprocessing. To build a classifier, a method of attribute selection is proposed to detect false alarms generated by the telecommunication system of the mine. Experiments were carried out on real data extracted from the telecommunication system operating in the copper mine of the KGHM Polska Miedź S.A.
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 77-87
Keywords: data mining; telecommunication system; data preprocessing; classification methods; inductive decision trees; detection of false alarms; decision rules; system telekomunikacyjny; drzewa indukcyjne; fałszywe alarmy; przygotowanie danych; reguły klasyfikacyjne